The algorithm for creation of 2d network - Kleiza, Vytautas; Kleiza, Jonas (Lietuvos matematikos rinkinys, 2005)
The research presents the program module for calculation of net area of 2d multiple connected region is created. The program is written in language of the mathematical package Maple.
Keywords: network; nodes; mathematical package Maple